Gaji Sebagai Objek Jaminan Utang di Bank Menurut Undang-Undang Jaminan Fidusia - Oryza Justisia Rizqy Winata; Yunanto Yunanto; Mujiono Hafidh Prasetyo (Magister Kenotariatan Universitas Diponegoro, 2021)
Fiduciary Guarantee Institutions have been widely used by the public as consumers and business actors, especially financing and banking companies. This article discusses the issue of the position of salary as an object of bank loan guarantee, and legal protection for the recipient of a fiduciary guarantee (creditor) with a Salary Guarantee if the fiduciary guarantee provider defaults according to Law Number 42 of 1999 on Fiduciary Guarantee. The research method used is normative juridical where the research refers to the norms contained in the legislation. Based on the results of the study, it was concluded that salaries as objects of debt guarantees in banking according to the Fiduciary Guarantee Act are categorized as recipients of rights as receivables, so that they can be used as objects of fiduciary guarantees. Banks in granting credit to civil servants and private employees/labor are required to make a Guarantee Deed at a Notary and registered at the Fiduciary Registration Office under the scope of the Ministry of Law and Human Rights, to provide legal certainty and protect the parties concerned. The bank anticipates losses due to default by insuring creditors at the time of submitting a credit application at the bank.Keywords: Salary: Receivables: Fiduciary GuaranteeAbstrakLembaga Jaminan Fidusia sudah banyak digunakan masyarakat sebagai konsumen maupun pelaku usaha terutama perusahaan pembiayaan dan Perbankan. Artikel ini membahas persoalan mengenai kedudukan gaji sebagai objek jaminan utang bank, dan perlindungan hukum terhadap penerima jaminan fidusia (kreditur) dengan Jaminan Gaji apabila pemberi jaminan fidusia wanprestasi menurut Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia. Metode penelitian yang digunakan adalah yuridis normatif dimana dalam penelitian mengacu kepada norma-norma yang terdapat dalam peraturan perundang-undangan. Berdasarkan hasil penelitian disimpulkan bahwa Gaji sebagai Objek Jaminan Utang di perbankan menurut Undang-Undang Jaminan Fidusia dikategorikan sebagai penerima hak sebagai Piutang, sehingga dapat dijadikan sebagai Objek Jaminan Fidusia. Pihak bank dalam pemberian kredit kepada pegawai negeri sipil dan karyawan swasta/buruh diharuskan dibuatkan Akta Jaminan di Notaris dan didaftarkan di Kantor Pendaftaran Fidusia di bawah lingkup Kementerian Hukum dan HAM, untuk memberikan kepastian hukum dan melindungi para pihak terkait. Pihak bank mengantisipasi kerugian akibat adanya wanprestasi dengan mengasuransikan kreditur pada waktu pengajuan permohonan kredit di bank.Kata Kunci : Gaji: Piutang: Jaminan Fidusia